Newborn Screening for Sickle Cell Disease Among Tribal Populations in the States of Gujarat and Madhya Pradesh in India: Evaluation and Outcome Over 6 Years - Thaker, Pallavi; Colah, Roshan B.; Patel, Jignisha; Raicha, Bhavesh; Mistry, Abhishek; Mehta, Vishal; Italia, Yazdi; Desai, Shrey; Dave, Kapilkumar; Shanmugam, Rajasubramaniam; Ghosh, Kanjaksha; Mukherjee, Malay B. (Frontiers in Medicine, 2022)
Sickle cell disease (SCD) poses considerable public health problems in India. This study was undertaken to understand clinical course of SCD among children identified during newborn screening programmes in Gujarat and Madhya Pradesh where the frequency of the HbS gene is high. A total of 8916 newborn babies 8411 from Gujarat and 505 from Madhya Pradesh were screened over 6 years (2010-2016) using HPLC and the diagnosis was confirmed by molecular analysis in a subset. A total of 128 babies (122 Gujarat, 6 Madhya Pradesh) were identified with sickle cell disease, of whom 87 (69 HbSS, 18 HbS- thalassemia) from Gujarat were followed for 0.5 - 6.5 years. Acute painful events, severe anemia and fever with infections were the major complications and 23 babies required hospitalization. Severe to moderate clinical presentation was found in 13.8% babies with SCD whereas, 86.2% babies had a milder presentation. Presence of ameliorating factors (α-thalassemia and Xmn I polymorphism) did not have a discernible effect on the clinical severity. Parents of babies with SCD were educated and counseled for home care. Distribution of mobile phones to 44 families having babies with SCD was beneficial as it allowed regular contact with patients and their families. Genetic counselling to the affected families has increased the awareness and acceptance for prenatal diagnosis and 18 couples opted for prenatal diagnosis in subsequent pregnancies. SCD is not always mild among tribal groups in India. Therefore facilities for early diagnosis and prophylactic treatment in the tertiary care centers should be made available. The difficulties in regular follow up of the babies in remote rural areas have also been highlighted.